Institutional Volume Thresholds and Risk‐Adjusted Outcomes After Transcatheter Aortic Valve Replacement: Contemporary Evidence From the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry - Sant Kumar; Ashish Pershad; Hursh Naik; Nezar Falluji (Journal of the American Heart Association, 2026)
Background The relationship between institutional volume and transcatheter aortic valve replacement outcomes is complex but vital for optimizing patient triage and developing effective care strategies. Methods The authors analyzed outcomes of patients undergoing transcatheter aortic valve replacement between January 2021 and February 2023 in the STS/ACC TVT (Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy) Registry at hospitals affiliated with the CommonSpirit Health network. Centers were categorized by annual TAVR volume as low (300 cases per year). Baseline risk assessment included the Society of Thoracic Surgeons score, an estimate of operative mortality risk. The primary outcome was major adverse cardiac and cerebrovascular events. Inverse probability of treatment weighting adjusted for baseline differences. Results Among 6663 patients, 58.6% were treated at high‐volume centers. Patients treated at high‐volume centers were older than those at intermediate‐ or low‐volume centers ( P